THE EFFECT OF INTERACTIVE VISUAL-BASED NUTRITION EDUCATION ON NUTRITION LITERACY AMONG PREGNANT WOMEN - Asirotul Marifah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Maternal nutrition literacy plays an important role in determining nutritional behavior during pregnancy. Inadequate nutrition literacy may increase the risk of chronic energy deficiency, anemia, low birth weight, and other adverse pregnancy outcomes. Interactive visual-based nutrition education has been developed as an innovative approach to improve understanding and retention of nutrition-related information among pregnant women. This study aimed to determine the effect of interactive visual-based nutrition education on nutrition literacy among pregnant women at Tambak Agung Auxiliary Health Center, Mojokerto. A quasi-experimental study with a one-group pretest-posttest design was conducted among 33 pregnant women selected through purposive sampling. Data were collected using the Nutrition Literacy Assessment Instrument for Pregnant Women (NLAI-P). The intervention consisted of PowerPoint videos, posters, 3D pop-up flipcharts, and “Isi Piringku” Velcro puzzle activities. Data were analyzed using a Paired Sample t-test with a significance level of 0.05. The results showed that the proportion of respondents with good nutrition literacy increased from 12.1% before the intervention to 72.7% after the intervention. The mean nutrition literacy score increased from 51.21 ± 11.42 to 76.85 ± 8.96. Statistical analysis revealed a significant difference between pretest and posttest scores (p < 0.001). Interactive visual-based nutrition education significantly improved nutrition literacy among pregnant women. This educational model can be considered an effective strategy to strengthen maternal nutrition promotion programs in primary healthcare settings.